On the semantics of Tarifiyt verbs of seeing - Maarten Kossmann (Journal of African Languages and Literatures, 2023)
The Amazigh (aka Berber) language Tarifiyt has two different roots for ‘to see’, ẓr, and wř, which are in partial complementary distribution depending on the aspect of the verb. In this article, the exact distribution of these verb roots is discussed for one paticular variety of Tarifiyt, that spoken in and around the city of Nador. It is shown that there are two, partially overlapping, verbs, one ‘to go/come and see’, which is always expressed by ẓr, and the other a general ‘see’ verb, which uses the root wř in the Imperfective stems, and ẓr in the Aorist and Perfective stems. However, the distribution is more complicated than that, and in the negation of irrealis events, Imperfective ẓr can also be used with the general ‘see’ verb. Moreover, it is shown that the choice of the aspect in the general ‘see’ verb is different in its details from that of other verbs, something that it may share with other verbs of experience perception.